Urban Public Space as an Art Object - Ptichnikova, Galina A. (Actual Problems of Theory and History of Art, 2018)
Architectural and spatial changes in city public space occurred during the 20th century. The emergence of new forms of the social and cultural life of the community is the main cause of these transformations. Nowadays typical of early 20th century cultural publicity is superseded by the mass “exodus” of people into privacy. The tendency for more privacy leads to the fact that the squares and streets cease to be a meeting place and a place for a dialogue, which moved into the closed space. In response to the cultural challenges, city public spaces changed or disappeared and new architectural and spatial constructs have been created. Artistic practices are among the modern methods of the resuscitation of public spaces. The objects of street art and public art that transform the streets, squares, industrial and transport areas are in the focus of our attention. The methods of the creation of art objects on the basis of the existing urban spaces are considered by the example of completed projects in Russia and abroad. Art allows us to create the new identity public spaces of the city turning it into the creative communications platform of an urban community. Works of art are powerful resources for the transformation of urban space, its redesign in line with the new needs of the society. New urban art objects do not fit the classic definition and are not determined by the traditional criteria. Urban art has reinterpreted public spaces and given rise to the new image of a modern city.